Influential Factors in Adherence to the Therapeutic Regime in Hypertension and Diabetes - Dora Inés Parra (Universidad de Antioquia, 2019)
Objective. To determine the factors associated with adherence to the therapeutic regime in patients with hypertension and type 2 diabetes mellitus cared for in primary care centers. Methods. This was an analytical cross-sectional study, conducted with 500 patients from two institutions in Bucaramanga (Colombia). Adherence to the therapeutic regime was measured with the label of Nursing outcomes “Treatment Behavior: Illness or Injury” and the instrument “Factors that influence on adherence to pharmacological and non-pharmacological treatments” by Ortiz Suárez was used. Results. Factors affecting negatively adherence to the therapeutic regime were: belonging to the subsidized regime, never being able to read written information about the management of their disease, and never receiving information about benefits of the medications ordered by the physician. On the contrary, positive influence was noted by referring “never” to the following statements, which impacted positively on adherence: the diverse occupations you have in and out of the house hinder your following the treatment; when your symptoms improve, do you interrupt the treatment? previously, have you had difficulties in complying with your treatment and believe there are difficult-to-change customs about foods and exercises? Conclusion. Two socioeconomic factors and one related with the health system and staff affected negatively on adherence to the therapeutic regime, while four factors related with the therapy favored it. The factors identified could be used in the design of nursing interventions to improve adherence in this population.